Achieving Student Educational dimension to the study of Mathematical Modeling - Cortés Cortés, Manuel; Iglesias, Miriam (Revista Universidad de Guayaquil, 2012)
Universities must respond to the increasing and continuous demands of Science and Technology and the production and the interests of culture. Its practitioners must be prepared to face the daily problems that arise in your work area should be able to organize, develop and manage the economy and fulfill the economic plans. That is why the universities in their academic training process should integrate the research work already, and structure their educational process with budgets from the standpoint of instructional and educational to help develop your career with comprehensive training that meets the heavy demands of his time. This paper addresses the above subject from the perspective of the teaching of applied mathematics and tries to give some ideas on resolving the problem of educational input in the teaching of mathematics in order to make them more interesting.
Keywords: Pedagogy